A didática do plurilinguismo e o repertório linguístico discente no ensino-aprendizagem do Português língua estrangeira: um encontro entre proficiência e formação para diversidade - CUNHA FILHO, Francisco Arimir Alves (Universidade Federal do Pará, 2020)
The main objective of this work is to ascertain to what extent a plurilingual didactic favors the learning of Portuguese as a foreign language in linguistically and culturally heterogeneous classes. Our data was generated from the recording of several didactical situations and interviews with students who evaluated the practices at the beginning until the end of the course. We chose to follow the qualitative model for data generation, description and analysis (CROKER, 2009; OLIVEIRA, 2015; DÖRNYEI, 2007). In addition, we use the multi-method approach to establish a dialogue between teaching actions and students' considerations (CRESWELL; CLARK, 2011; OLIVEIRA, 2015; SPRATT; WALKER; ROBISON, 2004). Action research is associated with ethnographic research (THIOLLENT, 2000; MONTAGNEMACAIRE, 2007; DÖRNYEI, 2007; JOHNSON, 1995). In relation to theoretical references, we utilize the concept of pluricultural and plurilingual competence, with a focus on linguistic, psycholinguistic and sociolinguistic aspects of hers (PY, 1991; DABÈNE, 1994; DEPREZ, 1994; MOORE, 1995; CASTELLOTTI; MOORE, 1997; COSTE; MOORE; ZARATE, 1997, 2009; CONSELHO DA EUROPA, 2001). In this perspective, we highlight the notion of linguistic repertoire of the plurilingual individual. Also, we betake the didactic and methodological guidelines of the actional approach and plural practices - gathered in so-called didactics of plurilingualism - to guide activities with the students (PICCARDO, 2014; CONSELHO DA EUROPA, 2001; BOURGUIGNON, 2012; PUREN, 2002; BLANCHET, 2014; CASTELLOTTI, 2010; CANDELIER, 2008; MEISSNER, 2002b). These ones come from African and Caribbean countries. They are plurilingual, two or more languages speaker. We take in account these prior knowledges to favor and improve their learning. We put in place actions susceptible to create a propitious environment to plurilingual practices. Throughout the course, we verified group's the more open positioning with regard to the didactics of plurilingualism: the alternation of languages, previously reserved, gradually became shared with us; little by little, students also started to understand and appreciate all their languages, no more barriers to learning, but partners in this process. These and others results through this research-action led us to consider viable and important the insertion of students‘ prior linguistic capital during their learning of portuguese, either to learn more effectively or to help them to become persons who respect all languages and cultures.